RETRACTED: Ascertaining the Influence of Lacto-Fermentation on Changes in Bovine Colostrum Amino and Fatty Acid Profiles - Vytautė Starkutė; Ernestas Mockus; Dovilė Klupšaitė; Eglė Zokaitytė; Saulius Tušas; Ramutė Mišeikienė; Rolandas Stankevičius; João Miguel Rocha; Elena Bartkienė (Animals)
The aim of this study was to collect samples of bovine colostrum (BCOL) from different sources (agricultural companies A, B, C, D and E) in Lithuania and to ascertain the influence of lacto-fermentation with Lactiplantibacillus plantarum strain 135 and Lacticaseibacillus paracasei strain 244 on the changes in bovine colostrum amino (AA), biogenic amine (BA), and fatty acid (FA) profiles. It was established that the source of the bovine colostrum, the used LAB, and their interaction had significant effects (p < 0.05) on AA contents; lactic acid bacteria (LAB) used for fermentation was a significant factor for aspartic acid, threonine, glycine, alanine, methionine, phenylalanine, lysine, histidine, and tyrosine; and these factor’s interaction is significant on most of the detected AA concentrations. Total BA content showed significant correlations with glutamic acid, serine, aspartic acid, valine, methionine, phenylalanine, histidine, and gamma amino-butyric acid content in bovine colostrum. Despite the differences in individual FA contents in bovine colostrum, significant differences were not found in total saturated (SFA), monounsaturated (MUFA), and polyunsaturated (PUFA) fatty acids. Finally, the utilization of bovine colostrum proved to be challenging because of the variability on its composition. These results suggest that processing bovine colostrum into value-added formulations for human consumption requires the adjustment of its composition since the primary production stage. Consequently, animal rearing should be considered in the employed bovine colostrum processing technologies.